APPLICATION OF POWTOON AUDIOVISUAL MEDIA IN MATHEMATICS LEARNING FOR ELEMENTARY SCHOOL STUDENTS: A REVIEW LITERATURE - Adi Candra Kusuma; Ratnasari, Nur; Noerismayanti, Noerismayanti (International Journal of Teaching and Learning, 2024)
The application Using Powtoon audiovisual materials in teaching elementary school pupils maths can be an interesting and effective method. Powtoon is an animated video creation platform that allows teachers to create engaging and interactive educational content. By using Powtoon, teachers can create learning videos that combine images, text, and sound to explain mathematical concepts visually and interestingly for students. One of the main advantages of implementing Powtoon is its ability to make learning material more interesting and easy for students to understand. With attractive animations and visuals, students can more easily understand complex mathematical concepts. Apart from that, the use of audiovisual media can also help students who have a visual or auditory learning style to more easily absorb information. This can increase student involvement in mathematics learning, because they can actively participate during the process of learning. Therefore, the use of Powtoon audiovisual materials in primary school mathematics instruction can provide a more interesting, interactive and effective learning experience for students, and help improve their understanding of mathematical concepts.